Epidemiology of hepatic encephalopathy in german hospitals – the EpHE study - Labenz, Christian; Wörns, Marcus-Alexander; Schattenberg, Jörn M.; Huber, Yvonne; Galle, Peter Robert; Labenz, Joachim; ALGK study group (Zeitschrift für Gastroenterologie, 2017)
Background Hepatic encephalopathy (HE) is a serious complication of liver cirrhosis. The proportion of patients with liver cirrhosis attending German hospitals suffering from HE is unknown.Methods In the first part of the study, data of 14 community hospitals and 5 university hospitals covering the years 2010 and 2011 were analyzed retrospectively for the DRG codes of liver cirrhosis and hepatic encephalopathy. In the second prospective part of the multicenter observational study, all patients with liver cirrhosis attending the departments of gastroenterology of 16 participating community hospitals within a study period of 3 months were included and screened for HE clinically according to the West Haven criteria (grades 1 – 4). Results A diagnosis of liver cirrhosis has been coded in 6366 cases in 2010 and in 7279 cases in 2011. In the vast majority of hospitals, less than 20 % of these cases had an additional DRG code for HE. Two hundred seventy-eight patients with liver cirrhosis were included into the prospective study. A clinically detectable HE was present in 36 % of the patients (n = 99). The majority was classified as West Haven 1 (n = 59, 59.6 %). Of the patients without clinical sings of HE, 48 % (n = 134) showed a pathological NCT.Conclusion Our data suggest that HE is underdiagnosed in German hospitals. Since treatment of HE may improve the prognosis of the patients as well as their quality of life, hospitalized patients with liver cirrhosis should be routinely screened for HE.
Keywords: Diagnosis related groups (DRG); Epidemiologie der hepatischen Enzephalopathie; Unterdiagnose der hepatischen Enzephalopathie; Zahlenverbindungstest